Hubungan Intensitas Penggunaan Media Sosial dengan Kesehatan Mental Mahasiswa PAI - Fasha, Yogi Zaini; Alfurqan, Alfurqan (Lembaga Yasin AlSys, 2024)
In the current era of information and communication technology development, internet users have become very easy. This is due to the need for access to information, lifestyle, communication and entertainment and knowledge available on various social media. Padang State University (UNP) which is an IT-Based University, an IT-based campus that no longer uses paper. Of course, making students use laptops, computers and mobile phones more often in carrying out lectures and also by providing unlimited internet or WIFI on campus makes students use it to play social media so that they forget time, which will make the level of intensity in using social media high and can be feared to increase the potential risk of mental health disorders. The purpose of this study was to describe the relationship between the intensity of social media use and the mental health of UNP PAI students class of 2023. This research uses quantitative methods with a quantitative descriptive approach. Data collection techniques were carried out by questionnaire through googleform. Data analysis used the product moment correlation formula through the SPSS version 26.0 for Windows programme. The research results obtained show that the value of Sig. 0.838 > α = 0.05 or Fcount value 0.030 < Ftable 0.273. This means that the higher the intensity of students in using social media, the higher their mental health. The same applies.